2017
DOI: 10.1039/c7nr05201d
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation and ambipolar electrical transport in GaAs/InSb core–shell nanowires

Abstract: The growth, crystal structure, strain relaxation and room temperature transport characteristics of GaAs/InSb core-shell nanowires grown using molecular beam epitaxy are investigated. Due to the large lattice mismatch between GaAs and InSb of 14%, a transition from island-based to layer-like growth occurs during the formation of the shell. High resolution transmission electron microscopy in combination with geometric phase analyses as well as X-ray diffraction with synchrotron radiation are used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…As for core@shell structures studied here, it is possible to employ molecular beam epitaxy [48] to achieve the growth of SiO 2 @InSb and Si@InSb MWs, in which the main stages are the growth of SiO 2 (or Si) core and InSb shell in succession. In terms of Si MWs, firstly, since the period's condition and radius of core are strictly required, the electron beam lithography and meta lift-off are suggested to determine the positions and sizes of catalysing metal particles [49] like Au or Cu, which are patterned on an oxide buffered layer thermally grown in Si(1 1 1) wafers.…”
Section: Feasible Methods To Fabricate Sio 2 @Insb and Si@insb Metala...mentioning
confidence: 99%
See 1 more Smart Citation
“…As for core@shell structures studied here, it is possible to employ molecular beam epitaxy [48] to achieve the growth of SiO 2 @InSb and Si@InSb MWs, in which the main stages are the growth of SiO 2 (or Si) core and InSb shell in succession. In terms of Si MWs, firstly, since the period's condition and radius of core are strictly required, the electron beam lithography and meta lift-off are suggested to determine the positions and sizes of catalysing metal particles [49] like Au or Cu, which are patterned on an oxide buffered layer thermally grown in Si(1 1 1) wafers.…”
Section: Feasible Methods To Fabricate Sio 2 @Insb and Si@insb Metala...mentioning
confidence: 99%
“…In the following, it is feasible to introduce the InSb shell covering the aforementioned Si or SiO 2 core, when the substrate temperature has already been tuned to the growth temperature of InSb. Under proper In rate and Sb flux, the thickness of InSb shell can be designed at will by choosing the growth time reasonably [48,54]. Finally, with all the processes going successfully, it can be expected to obtain 1D SiO 2 @InSb and Si@InSb microwires.…”
Section: Feasible Methods To Fabricate Sio 2 @Insb and Si@insb Metala...mentioning
confidence: 99%
“…In addition, the thickness of the shell can be employed to modulate the electrical behaviors of transistors based on GaAs/InSb core–shell nanowire. Rieger et al demonstrated that the electrical performance of transistors based on GaAs/InSb core–shell nanowire was determined by the energy band of InSb shell rather than GaAs core . They also discovered that Fermi level shift was induced when the thickness of InSb shell gradually changed.…”
Section: Inorganic Semiconducting Materialsmentioning
confidence: 99%
“…Nevertheless, recent studies have focused on understanding the strain relaxation and morphology transitions in lattice-mismatched core-shell NWs. 20,21 Regulating absorption by regulating the morphology variations in core-shell NWs (e.g. GaP/GaAs 22,23 ) is a promising route for developing novel photovoltaic and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%